Pengaruh Perceived Usefulness dan Perceived Ease of Use terhadap Continuance Intention to Use Mobile Banking dengan Trust sebagai Variabel Intervening (Studi pada Pengguna Aplikasi Bank Jambi Mobile di Kota Jambi) - Febby Nanda Utami; Yossinomita; Nia Rahayu (Jurnal Ilmiah Manajemen dan Kewirausahaan (JUMANAGE), 2022)
This research aims to determine the direct or indirect effect of perceived usefulness and perceived ease of use on continuance intention to use of the Bank Jambi Mobile application, with trust as the intervening variable. The research sample used was 96 respondents, where data from the sample was collected using a questionnaire and then analyzed using the partial least squares path modeling (PLS) technique. The results of the direct influence test prove that perceived usefulness has no significant effect on trust, while perceived ease of use has a significant effect on trust. Meanwhile, trust has a significant effect on continuance intention to use. For the mediating effect of the trust variable, it is proven that trust can mediate the indirect effect between perceived ease of use on continuance intention to use. However, it cannot mediate the indirect effect of perceived usefulness on continuance intention to use. The results of the study have implications for the efforts of the management of Bank Jambi as an application provider to increase the benefits and ease of use of the Bank Jambi Mobile application, as well as public trust in the application.